Investigating the Effect of Using Facebook Texting on EFL Learners’ Academic Writing The Case of Second Year LMD Students of English at the University of Souk-Ahras - OUARTI, Dhikra (My University, 2023)
Abstract This current study aims to investigate the effect of Facebook texting on second year students of English’ academic writing. Additionally, it sought to investigate the features of Facebook texting that appear in students’ academic writings. In order to test the main hypotheses, the researcher opted for a mixed method approach, consisting of two instruments; a questionnaire for n40 students chosen randomly from N98 second year students of English at the university of Souk-Ahras, and an interview with four (04) teachers of written expression and comprehension module selected conveniently from the same university. The gathered data unearthed that the overuse of Facebook texting has a negative effect on students’ academic writing, which manifests in the use of informal language, abbreviations and acronyms, overuse or absence of punctuation, and the lack of respect for grammar rules. Based on these results, the hypotheses were confirmed. ----------------- ملخص تهدف الدراسة الحالية إلى التحقيق في تأثير الرسائل عبر فيسبوك على الكتابة الأكاديمية لطلاب في السنة الثانية من تخصص اللغة الإنجليزية. بالإضافة إلى ذلك، تهدف الدراسة إلى التحقيق في سمات رسائل فيسبوك التي تظهر في كتابات الطلاب الأكاديمية. ومن أجل اختبار الفرضيات الرئيسية، اختار الباحث أداتين؛ استبيان لـ 40 طالبًا تم اختيارهم بشكل عشوائي من بين 98 طالبًا من طلاب السنة الثانية في تخصص اللغة الإنجليزية في جامعة سوق أهراس. مقابلة مع أربعة (04) معلمين لوحدة التعبير الكتابي وفهم المقروء تم اختيارهم بشكل مناسب من نفس الجامعة. كشفت البيانات التي تم جمعها أن استخدام الرسائل عبر فيسبوك بشكل مفرط يؤثر سلبًا على الكتابة الأكاديمية للطلاب ويتجلى ذلك في استخدام اللغة غير الرسمية والاختصارات والاستخدام المفرط أو عدم استخدام الترقيم وعدم الالتزام بقواعد النحو. بناءً على هذه النتائج، تم تأكيد الفرضيات ------------------- Résumé Cette étude actuelle vise à étudier l'effet de la messagerie Facebook sur l'écriture académique des étudiants de deuxième année d'anglais. De plus, elle cherchait à examiner les caractéristiques de la messagerie Facebook qui apparaissent dans les écrits académiques des étudiants. Pour tester les hypothèses principales, le chercheur a opté pour deux instruments : un questionnaire destiné à 40 étudiants choisis au hasard parmi 98 étudiants de deuxième année d'Anglais de l'université de Souk-Ahras. Une interview avec quatre (04) enseignants du module d'expression écrite et de compréhension choisis de manière pratique dans la même université. Les données recueillies ont révélé que l'abus de la messagerie Facebook a un effet négatif sur l'écriture académique des étudiants, qui se manifeste par l'utilisation d'un langage informel, d'abréviations et d'acronymes, d'une ponctuation excessive ou absente, et d'un manque de respect pour les règles grammaticales. Sur la base de ces résultats, les hypothèses ont été confirmées.